The use of ICT in achieving the Millennium Development Goals (MDGs) in Universities - Kaino, Luckson Muganyizi (South African Journal of Higher Education, 2016)
The contribution of Information and Communication Technology (ICT) in achieving the Millennium Development Goals (MDGs) and the contribution of higher education institutions in achieving these have been emphasized. This study sought to find out the extent to which university-based researches on ICTs addressed and impacted the three MDGs of gender balance, education development and social and economic development in the target communities. The study was descriptive in nature and used both qualitative and quantitative in design using questionnaires, structured interviews and documentary schedules. The findings of the study showed that sensitivity to gender balance was an incidental matter, ICT applications were a means to extend access to wider educational opportunities, information and communications, and these studies added value to primary local economic resources and productivity-related socio-economic activities. It was concluded that the studies surveyed did make some positive contributions towards the MDGs agenda and the impact was generally not direct.